Various topological phases and their abnormal effects of topological acoustic metamaterials. Issue 2 (9th February 2023) - Chen, Yan‐Feng; Chen, Ze‐Guo; Ge, Hao; He, Cheng; Li, Xin; Lu, Ming‐Hui; Sun, Xiao‐Chen; Yu, Si‐Yuan; Zhang, Xiujuan
Abstract: The last 20 years have witnessed growing impacts of the topological concept on the branches of physics, including materials, electronics, photonics, and acoustics. Topology describes objects with some global invariant property under continuous deformation, which in mathematics could date back to the 17th century and mature in the 20th century. In physics, it successfully underpinned the physics of the Quantum Hall effect in 1984. To date, topology has been extensively applied to describe topological phases in acoustic metamaterials. As artificial structures, acoustic metamaterials could be well theoretically analyzed, on‐demand designed, and easily fabricated by modern techniques, such as three‐dimensional printing. Some new theoretical topological models were first discovered in acoustic metamaterials analogous to electronic counterparts, associated with novel effects for acoustics closer to applications. In this review, we focused on the concept of topology and its realization in airborne acoustic crystals, solid elastic phononic crystals, and surface acoustic wave systems. We also introduced emerging concepts of non‐Hermitian, higher‐order, and Floquet topological insulators in acoustics. It has been shown that the topology theory has such a powerful generality that among the disciplines from electron to photon and phonon, from electronic to photonics and acoustics, from acoustic topological theory to acoustic devices, could interact and be analogous to fertilize fantastic new ideas and prototype devices, which might find applications in acoustic engineering and noise‐vibration control engineering in the near future. Abstract : As an interdisciplinary example, topological acoustic metamaterials, combining topological concept, energy band structures, and acoustics with microstructured materials, exhibit various phases, including quantum Hall effect, topological insulator (TI), topological semimetal families, higher‐order, non‐Hermitian, and Floquet TIs, which show many abnormal effects to offer unconventional ways to control acoustic waves. These phases have been realized in systems, such as airborne acoustics, solid elastic waves, and surface acoustic waves.